Camel milk and its allied health claims: a review - Sakandar, Hafiz Arbab; Ahmad, Sarfraz; Perveen, Rashida; Aslam, Hafiz Khuram Wasim; Shakeel, Azam; Sadiq, Faizan Ahmed; Imran, Muhammad (Progress in Nutrition, 2018)
Camel milk is one of the most important milk among other mammal’s milk due to its nutraceutical attributes. It has high concentration of iron which makes it panacea for those who have iron deficiency anemia. The salts present in camel milk has significant effect on human health. It is used for various diseases in urban areas of developing countries. It is a potential functional food. In urban areas of developing economies it is used for ascites. Camel milk is unique from other ruminant milk in terms of composition as well as functionality, as it contains high concentration of immunoglobulins and insulin. People with enervated immune system and those who are lactase-deficient can consume camel milk without any allergic response. Moreover, it is also used for potential therapeutic properties such as efficacy against diabetes and cancer as well as having anti-hypertensive properties.